Prognosis of acute myocardial infarction in patients on hemodialysis stratified by Killip classification in the modern interventional era (focus on the prognosis of Killip class 1) - Takasaki, Akihiro; Kurita, Tairo; Hirabayashi, Yosuke; Matsuo, Hiroshi; Tanoue, Akiko; Masuda, Jun; Yamanaka, Takashi; Katayama, Kan; Machida, Hirofumi; Ichikawa, Takehiko; Ito, Masaaki; Dohi, Kaoru (Heart and vessels, 2022)
Cardiovascular events and death are more prevalent in hemodialysis (HD) patients than in the general population. However, a detailed prognostic risk stratification of HD patients with acute myocardial infarction (AMI) has not yet been performed in the modern interventional era. We examined 4509 AMI patients (89 AMI/HD and 4420 AMI/non-HD) from the Mie ACS registry and detailed prognostic analyses based on the Killip classification were performed (Cohort A). In addition, prognosis of Killip class1 AMI/HD was compared with those of 313 non-AMI/HD patients from the MIE-CARE HD study using propensity score-matching method (Cohort B). Primary endpoint was all-cause mortality for up to 2 years. All-cause death occurred in 13.0% of AMI/non-HD and 35.8% of AMI/HD during follow-up, and patients with Killip class 1 had lower 30-day and 2-year mortality than those with Killip class ≥ 2 in both AMI/non-HD and AMI/HD. Cox regression analyses identified that Killip class ≥ 2 was the strongest independent prognostic factor of 30-day mortality with a hazard ratio of 7.44 ( p < 0.001), whereas both presence of HD and Killip class ≥ 2 were the independent prognostic factors of mortality for up to 2 years. In Cohort B, a propensity score-matching analysis revealed similar all-cause mortality rates between Killip class 1 AMI/HD and non-AMI/HD. In HD patients with Killip class 1 AMI, 30-day mortality was around 6%, and long-term mortality among 30-day survivors after AMI was comparable with the natural course of HD patients in the modern interventional era. Clinical trial registration: URL: https://www.umin.ac.jp/ctr/index-j.htm . UMIN000036020 and UMIN000008128